Formaldehyde and cognition - He, Rongqiao (Springer, 2017)
This book introduces important, new knowledge regarding formaldehyde, especially endogenous formaldehyde, revealing its many key roles in the human body. It reviews the relationship between endogenous formaldehyde and cognition as well as age-related cognitive impairment, by discussing different aspects such as formaldehyde metabolism, its function in the brain, links with epigenetics and neurophysiology, and epidemiological and clinical investigations. The author also provides suggestions on how to prevent cognitive impairment resulting from excess endogenous formaldehyde. This book appeals to all readers who are interested in cognitive science and toxicology.
Keywords: Formaldehyde -- Effectiveness.; Cognition.; elektronické knihy; electronic books